Nalar Teologis dan Hukum Islam Bias Gender - Muh Rusli; Muhammad Thahir; Asriadi Zainuddin (Al-Ulum, 2013)
One of the core teachings of the Qur'an is the dignity of human beings are equal before God, regardless of differences in gender (men and women). What distinguishes the two is the quality of piety. Substancely, gender discourse is not new in Islam. When the degrees are equal before God, then men and women should be able to establish a good working relationship without harming each other. Among the causes of the persistence of the Muslim understanding that gender bias is a false construct understanding in interpreting the word of God and the Hadith of the Prophet which then legitimized by Islamic laws. To that end, contextual reinterpretation of any gender bias arguments to be conducted. The reinterpretation considering the current situation and the principle of mutual benefit, thus giving birth to a new paradigm of meaning and gender-equitable and aligned with the universal values of Islam.